Analysis of biological development - Klaus Kalthoff (McGraw-Hill, 1996)
The organization of the book reflects the union of classical and modern ways of analysis in contemporary developmental biology. Part One emphasizes classical methods of analysis and covers the series of embryonic stages from gametogenesis to histogenesis. Part Two introduces the genetic and molecular analysis of development. Part three combines classical and modern types of analysis. This part features on pattern formation, cell differentiation, sex determination, hormonal control, growth, and the roles of cell adhesion and extra cellular materials in morphogenesis